Perizinan Berusaha di Daerah Pasca Undang-undang Cipta Kerja - Nanditamaha Mulia Alodia Saraswati; I Nyoman Gede Sugiartha; Ida Ayu Putu Widiati (Jurnal Preferensi Hukum, 2024)
Licensing is a document that proves the legality of allowing a person or group of people to carry out legal actions, even though it is contrary to statutory regulations. To create a business we need a business permit which functions as the legality of the business and as a legal umbrella for implementing it. The formulation of the problem raised is: How are business licensing arrangements in regions before and after the Job Creation Law? What are the procedures for issuing business permits in regions after the Job Creation Law? This thesis research uses normative legal research methods. The research results show that the procedures for issuing business permits in the regions before the Job Creation Law were PTSP (One-Stop Integrated Service), INSW (Indonesian National Single Window), and OSS (Online Single Submission). Meanwhile, the procedure for issuing business permits after the Job Creation Law is OSS RBA (Online Single Submission-Risk Based Approach. The basis for determining the issuance of business permits in regions is based on risk, namely low, medium low, medium high, high risk. Procedures for issuing business permits In post-Job Creation Law areas, there are several risk determinations and activity scale rankings.